Development and implementation of a wetlands volunteer monitoring pilot program for Oklahoma - Breetzke, Erin Elizabeth (My University, 2000)
Due to limited public and private manpower,citizens have become valuable tools for collecting environmental data. Currently over 700 volunteer environmental monitoring programs in the United States are actively collecting data in various ecosystems to be used by governments and university scientists in order to develop legislation or for use in research. Oklahoma currently has three active volunteer environmental monitoring programs, none of which specifically monitors wetland ecosystems. As stated in the Oklahoma Comprehensive Wetlands Conservation Plan, a goal has been set forth to develop and implement a wetland volunteer monitoring program for the state. This research details the development and implementation of the Wetland Health Assessment Monitoring (WHAM) Program. Through the cooperation of Oklahoma state environmental program directors, as well as directors nationwide, parameters, methods,and associated quality assurance protocols were selected for the program's addendum. The implementation of this pilot program produced valuable feedback and information needed to assure the program is meeting its goals. It is expected that the WHAM Program, when implemented statewide, will become beneficial in assessing the condition of Oklahoma's wetland resources.
Thesis (M. Env. Sci.)--University of Oklahoma, 2000.
Includes bibliographical references (leaves 204-205).
Keywords: Wetland conservation; Environmental monitoring--Oklahoma; Volunteer workers in conservation of natural resources--Oklahoma; Volunteer workers in environmental protection--Oklahoma